ChemInform Abstract: Consecutive Gold(I)‐Catalyzed Cyclization Reactions of o‐(Buta‐1, 3‐diyn‐1‐yl‐)‐Substituted N‐Aryl Ureas: A One‐Pot Synthesis of Pyrimido[1, 6‐a]indol‐1(2H)‐ones and Related Systems. Issue 40 (12th September 2013) - Sharp, Phillip P.; Banwell, Martin G.; Renner, Jens; Lohmann, Klaas; Willis, Anthony C.
Abstract Treatment of readily available o‐(buta‐1, 3‐diyn‐1‐yl)‐substituted N‐aryl ureas with Echavarren′s gold(I) catalyst under microwave irradiation affords, via a twofold cyclization process, pyrimido[1, 6‐a]indol‐1(2H)‐ones.